Microwave-assisted synthesis of vanadium and chromium carbides nanocomposite and its effect on properties of WC-8Co cemented carbides. (15th July 2016) - Zhao, Zhiwei
Abstract: A new method of in-situ microwave heating is used to prepare vanadium and chromium carbides (V8 C7 -Cr3 C2 ) nanocomposite and their alloys. The as-prepared nanocomposite was used as the grain growth inhibitor of cemented tungsten carbides. Well dispersed V8 C7 -Cr3 C2 nanocomposite with a mean diameter of about 30 nm can be synthesized at lower temperature. The prepared nanocomposite has an important effect on the microstructure and properties of WC-8Co alloys. The microstructure of WC-8Co-0.8(V8 C7 -Cr3 C2 ) alloys is more uniform than that of WC-8Co alloys. Vickers hardness and fracture toughness of the former can be increased by about 7% compared with those of the latter. Graphical abstract: